Inadequate adaptation of geospatial information for sustainable mining towards agenda 2030 sustainable development goals. (20th November 2019) - Moomen, Abdul-Wadood; Bertolotto, Michela; Lacroix, Pierre; Jensen, David
Abstract: For all the evolutionary ages of mineral resource development, there have not been concerns about sustainable mining until the 21st century. Thus, this paper explores the extent to which emerging geospatial technologies have been deliberately used in the mining industry activities to achieve the United Nations Agenda 2030 Sustainable Development Goals. Governments, the mining industry, Non-Governmental and International Organisations have various investments in geospatial programmes and technologies for Environmental and Social Impact Assessments and baseline studies to enhance the achievement of these goals. However, these efforts prove inadequate to link the social, environmental and economic baseline analysis of sustainable development goals. The observations in this paper, therefore, have been obtained largely from extensive literature review to gain a broad understanding of previous and current applications of emerging technologies in the field. The literature has been explored in two successive steps. First, the literature was broadly queried to find the most current works on sustainable mining for three decades (i.e. 1990 to 2019). Second, out of over 100 papers, reports, and books retrieved in the first step, a more specific search and analysis of existing academic and industry literature on the explicit applications of emerging geospatial technology for enhancing sustainable development in the mining sector was conducted. In spite of its ensemble of capabilities for multivariate analysis, analysis of the literature reveals that there is inadequate adaptation of emerging geospatial technologies, which can simultaneously measure and link generally acceptable social, economic and environmental costs and benefits of mining for sustainability considerations in a local setting. There is a dearth of literature that discuss this new approach in addressing sustainable mining. Findings of this paper shall, therefore, inform the scientific community, industry, Non-Governmental Organisations and consultants on emerging approaches to address salient issues of sustainable mining towards meeting the agenda 2030 SDGs. Highlights: Lack of systems to concurrently measure the triple-bottom-line in sustainable development. The triple bottom-line can be simultaneously measured with the evolving geospatial tools. There is inadequate application of geospatial technology on a sustainable mining agenda. No adequate efforts from governments, industry, NGOs and International Organisations. Uncertainty remains in adapting geospatial technology solely for sustainable mining.